PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA DI KANTOR REGIONAL VI BADAN KEPEGAWAIAN NEGARA MEDAN - NIRMA ROSALIA; ABDUL MUIN SIBUEA; SYAHYUNAN . (JURNAL ILMIAH MAKSITEK, 2021)
This study aims to test empirically the effect of work competence and discipline on the performance of the state civilservants. This research uses a descriptive approach. Population and sample, respectively 95 people and 30 people. Thetypes of data used are primary data and secondary data. Data collection techniques consisted of questionnaires, interviews,literature study, and documentation study. Tests performed on this research is a validity test and reliability test, classicalassumption test includes normality test, multicollinearity test, and heteroscedasticity test, hypothesis testing which includesthe F test and t test, multiple linear regression analysis, and the coefficient of determination R². From the research results, itis obtained that the results of multiple linear regression. The results showed that the variable competence and workdiscipline affected employee performance 86.3% and the remaining 13.7% was influenced by other factors not examined.